An Analysis 21st Century Skill Of Pre-Service Teachers Readines In The English Language Education Study Program State Islamic University Of Mataram - Kurniajaya, Setiawan; Ika Rama Suhandra; Soni Ariawan (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This research aims to analyze the perspectives of seven English Education students at the State Islamic University of Mataram regarding the significance of 21st-century skills in education. The respondents are pre-service teacher were above 7th semester unanimously agree that mastering these skills is essential for pre-service teachers, especially in the context of English language learning. They emphasize that such skills enhance educational quality through technology, foster creativity, and prepare students to face global challenges. The integration of technology into educational practices is highlighted as crucial for improving learning outcomes and increasing student engagement. The practical application of 21st-century skills during teaching practice illustrates how these pre-service teachers incorporate critical thinking, communication, collaboration, and creativity alongside technological tools. Many participants advocate for student-centered approaches that encourage critical thinking and effective communication, utilizing digital resources to enhance interactions. The importance of digital platforms for promoting teamwork among students is also noted, reflecting a collaborative learning environment. Furthermore, the proactive engagement of these students during their Field Experience Practice Program demonstrates their readiness to apply these skills in real-world teaching scenarios. The successes reported in implementing 21st-century skills during this program underscore the effectiveness of their educational preparation and suggest a positive outlook for their future careers as educators.